Modeling water hyacinth growth dynamics - Milićević, Dragan B. (Archives of Biological Sciences, 2023)
Paper description: Water hyacinth growth studies have mostly been performed for climatic conditions that favor its rapid growth. The aim of the study was to obtain an understanding of the dynamics of plant growth in a moderate-continental climate. The wet biomass of plants was measured, statistical analysis of the data was performed, and the parameters of the model were defined. A model of biomass growth dynamics was obtained. The results are of essential importance for the application of water hyacinths for the purification of wastewater under conditions of a moderate-continental climate. Abstract: This study aimed to evaluate the biomass growth of water hyacinth (Eichhornia crassipes [Mart.] Solms) under partially controlled conditions during a 70-day test using a mixture of municipal wastewater and water from a shaft as a source of nutrients. The water hyacinth in a moderately continental climatic condition at a latitude of 43oN can achieve productivity of an average of 18.25 kg/m2 in partially controlled conditions, whereas under natural conditions and under conditions of controlled harvesting, larger amounts of biomass can be obtained. Considering the large amounts of biomass of over 1.5 t/ha per day, i.e. over 180 t/ha per year, produced, water hyacinth can be successfully used in wastewater treatment plants with very favorable economic effects if the biomass generated is used for energy production, as a nutrient or food, and for many other needs. The following models were used to model the dynamics of water hyacinth biomass growth: the exponential model (average MSE 0.3117, average R2 to 0.9793), second-order polynomial model (average MSE 0.0952, average R2 0.9937) and logistic model (average MSE 0.0508, average R2 0.9966). All models have high accuracy; however, the exponential model and the second-order polynomial model give a continuous increase in biomass over time, practically to infinity, without taking into account that under conditions of increased plant density and reduced availability of resources, biomass growth slows down, and therefore, they are not suitable for application in real conditions. The logistic model (average environmental capacity 18.25 kg/m2, average growth rate 0.0571 g/g·day after about 150 days) adequately describes the growth of water hyacinth biomass with high accuracy, which enables the monitoring and control of the process operation and the achievement of the required quality of the treated wastewater.